Effect of Variation in Concentration of SCOBY Kombucha Gel Citrus Peel Extract (Citrus nobilis) on Wound Incision (Vulnus Scissum) in Mice (Mus musculus) - Shofiyya, Ainina Neihayatus; Eva Agustina; Funsu Andiarna; Irul Hidayati; Risa Purnamasari (Hasanuddin University, 2025)
A laceration wound is damage to the skin tissue characterized by a neat outline of the wound edge, due to slices by sharp instruments or incisions during surgery. This study aims to evaluate the effect of variations in the concentration of SCOBY Kombucha gel preparations of orange peel extract (Citrus nobilis) on wound healing (Vulnus Scissum) in mice (Mus musculus). SCOBY Kombucha gel was made with six concentration variations (0%, 2%, 4%, 8%, 10%, and 12%) and tested for its effectiveness in accelerating wound healing. The research method involved making incision wounds on male mice, followed by applying the gel according to the specified concentrations. The results showed that SCOBY Kombucha gel with a concentration of 12% was most effective in accelerating wound healing, approaching the effectiveness of the positive control (bioplacenton). Analysis showed that the increase in gel concentration was directly proportional to the effectiveness of wound healing, where higher concentration gels showed significantly faster wound closure.